Stereoselective (4 + 3) cycloadditions of allenyl ethers-furans by chiral auxiliaries inducing and evaluation of anti-breast cancer activity - Lei, Wenli; Song, Yuyang; Long, Ai; Que, Yanyan; He, Shuzhong; Zhong, Hang; Chen, Yang (Frontiers in Plant Science, 2022)
The medicinal plants were wildly library of natural products in drug discovery. The most active molecules with seven-membered rings skeleton represent a challenge for construction. A stereoselectivity (4 + 3) cycloadditions between allenyl ethers and substituted furans induced by chiral auxiliaries has been investigated. And the results showed significant stereoselectivities and regioselectivities. The optical cycloadducts with an oxygen-substituted seven-membered ring framework were generated by removing chiral auxiliaries under acidic conditions. The antiproliferative activity of the novel compounds displayed moderate antiproliferative effects toward T47D cells.